2012
DOI: 10.1002/sia.4916
|View full text |Cite
|
Sign up to set email alerts
|

Physical characterization of sub‐32‐nm semiconductor materials and processes using advanced ion beam–based analytical techniques

Abstract: The authors have addressed the application of advanced ion beam-based analytical techniques to various physical characterization aspects in sub-32-nm semiconductor front-end-of-line materials and processes. We have presented the application of 18 O-isotope labeling in combination with SIMS depth profiling to follow O-migration in high-k/metal gate stacks. We have also demonstrated the application of complementary low-energy ion scattering and time-of-flight SIMS surface analysis to determine high-k thin film c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Again, the use of other techniques such as transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), MEIS, atom probe as well as analysing samples in a ''backside'' configuration are important to overcome sputtering and ion-yield artefacts. 103 Cesium cluster ''MCs'' analysis: the analysis of Cs 1 or Cs 2 1 ions associated with the element of interest is often used for the characterisation of II-VI and III-V multilayers 104 for optoelectronic applications. This is mainly due to reduced matrix effects and easier quantification, but can also be used on magnetic instruments that are not equipped with a floating Cs column to obtain relatively low impact energies (typically in the 500 eV to 4 keV range).…”
Section: Microelectronicsmentioning
confidence: 99%
“…Again, the use of other techniques such as transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), MEIS, atom probe as well as analysing samples in a ''backside'' configuration are important to overcome sputtering and ion-yield artefacts. 103 Cesium cluster ''MCs'' analysis: the analysis of Cs 1 or Cs 2 1 ions associated with the element of interest is often used for the characterisation of II-VI and III-V multilayers 104 for optoelectronic applications. This is mainly due to reduced matrix effects and easier quantification, but can also be used on magnetic instruments that are not equipped with a floating Cs column to obtain relatively low impact energies (typically in the 500 eV to 4 keV range).…”
Section: Microelectronicsmentioning
confidence: 99%
“…After some silicon is deposited on the sample surface and most of the initial substrate is removed from the back side until getting close to the interface of interest, the newly prepared surface for the back-side depth profile needs to be parallel to all interfaces and to the initial sample surface. , This technique has been applied to various systems, including Ge/Pd ohmic contacts on InP, the segregation of boron toward the silicon surface, and the characterization of HfO 2 , and HfSiO 2 thin films. This work is still ongoing for the current generation of devices in which it is applied to high-mobility III–V channel materials …”
Section: Introductionmentioning
confidence: 99%
“…This work is still ongoing for the current generation of devices in which it is applied to high-mobility III−V channel materials. 32 In the present work, the origin of the diffusion of metal species into the organic layer as well as the influence of sample properties on these mechanisms is investigated in order to develop reliable protocols for the characterization of multilayered metal−organic devices. The silver diffusion has been studied for various sample compositions, for films deposited at two different temperatures, and for different impact energies during SIMS depth profiling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The scaling of semiconductor device technology leads to an increase in the number of materials used and frequently also in a reduction of their thickness such that elemental/compositional depth profiling demands a higher sensitivity, better quantification and higher depth resolution . Recent studies using secondary ion mass spectrometry (SIMS) for these applications have shown that using reactive primary ions such as oxygen or cesium with extremely low‐impact energy may provide a solution to these requirements . It has now extensively been established that when using a Cs beam, the near‐surface Cs concentration, C Cs , influences the ionization yield of not only the negative ions but also of the positive and even the molecular ions, be it with scaling factors which depend on the materials under investigation .…”
Section: Introductionmentioning
confidence: 99%